Trends and Tendencies in the Field of Improving the HR-Systems of Hungarian Public Universities - József Poór; Andrea Bencsik; Iván Fekete; Gyula László; Zoltán Majó (Revista de Management Comparat International)
In recent years it has become accepted that, besides traditional success factors, human resource management (HRM/HR) plays an increasingly important role in organizational success and in retaining and improving domestic and international competitiveness (Gordon-Whitchurch, 2007). In the countries of the developed world especially in the case of anglo-saxon pioneers the public sphere (including universities) has left the normative bureaucratic-administrative Taylorian system, that is based on formal regulation, far behind (Farkas et al, 2003). These efforts provided models and experience that were applicable in the transforming countries of Europe, including Hungary. In view of the above, we intended to make a non-exhaustive overview based on the sources of literature and the practices of 11 Hungarian universities of the change of the situation of HR and the possibilities of its modernization in this field.